Direito à saúde baseada em evidências - José Renan da Cunha Melo (2022)
The health judicialization in Brazil is increasing in an exponential way in the past ten years. The Justice decision in judicial actions on Right to Health in general does not take into consideration the available literature-based scientific data and most of the time is based either on subjective aspects or on formal procedural arguments. In order to evaluate the influence of Medicine-Based Evidence (MBE) on the judicial first and second instances a data survey of sentences regarding the right to health of both Federal and State Courts, as well as the sight of technical staff from the Technical Support Nuclei (NATs) created by the Brazilian National Council of Justice (CNJ) to give technical support to judges in right to health law suits. Considering MBE works based on empirical scientific data the aims of the present work is the use of this approach for obtaining objective and scientifically proved data which should be used by the Judiciary system as a base for the decisions in this area of knowledge. Methods: The study was done by lawsuits of judicial processes concerning five categories of events data survey: medical error, in-hospital admission, medicines, medical procedures, and others. A total of 1151 judicial sentences and 1002 Technical Notes from the NATs were analyzed. 831 sentences (72.2%) were judged at the State Courts whereas 320 (27.8%) by the Federal Courts. Concerning the Technical notes 615 (61.4%) and 387 (38,7%) belonged to State and Federal Courts respectively. The sentences were classified according to the judicial provision or no-provision. Part of the decisions were without resolution of judicial merits. The technical notes were classified as favorable or unfavorable. Results: From 1151 sentences, 864 (75.0%) have been given judicial provision, 207 (18,0%) have gotten no-provision, and 80 (7,0%) of the processes were extinguished without resolution of judicial merits. 481 out of 1002 (48.0%) Technical Notes had favorable indications and 521 (52.0%) unfavorable opinions. The judges sentencing only have referred the term MBE on sentencing in 30 (2,6%). There were 391 cases (33.9%) of judicial appeals to the second instance courts. In 325 (83.1%) the first instance decision was maintained. Conclusion: The data seem to indicate that in right to health cases the judges decide without using the objective and scientific data available in the medical literature and known as evidence-based medicine in 97.4%. Therefore, the decisions are made on an intuitive inductive basis. Although the mechanisms created by CNJ to provide support to magistrate decisions, such as technical notes from NATJus are technically well organized judgements, they do not necessarily take into account the hierarchy of evidence established by EBM for assessing qualitative health research, compromising the justice in the judicial decisions concerning the right to health.